The Influence Of Digital Ecosystems And Its Impact On Local Economic Growth: A Regional Economic Perspective - Syamsu Rijal (International journal of technology and education research, 2025)
This article explores the impact of digital ecosystems on local economic development with a focus on a regional perspective. Data is collected from various sources and analyzed to understand the relationship between digital ecosystem development and economic growth in various regions. The research results show that the development of a digital ecosystem has a significant positive impact on local economic growth through increasing productivity, job creation and innovation in the SME sector. This research approach is qualitative, using secondary data from journals, reports and other reliable sources. Data analysis was carried out by identifying the main themes that emerged from the literature. Data analysis was carried out using a thematic approach, where the main themes emerging from the literature were identified and analyzed. These themes include ICT infrastructure, innovation and SMEs, education and digital skills, and government policy. Each theme is analyzed to understand how digital ecosystems influence local economic development in various regional contexts.